Impact of air gun noise on the behaviour of marine fish and squid - Fewtrell, Jane; McCauley, Robert (Pergamon, 2012)
In this study various species of captive marine fish and one species of squid were exposed to the noise from a single air gun. Six trials were conducted off the coast of Western Australia with each trial using a different noise exposure regime. Noise levels received by the animals ranged between 120 and 184 dB re 1 μPa2.s (SEL). Behavioural observations of the fish and squid were made before, during and after air gun noise exposure. Results indicate that as air gun noise levels increase, fish respond by moving to the bottom of the water column and swimming faster in more tightly cohesive groups. Significant increases in alarm responses were observed in fish and squid to air gun noise exceeding 147–151 dB re 1 μPa SEL. An increase in the occurrence of alarm responses was also observed as noise level increased.